Critical success factors of expatriations by Malaysian international corporations / Senian Malie ... [et al.] - Malie, Senian; Awang Shuib, Awang Rozaimie; Mohd Esa, Isma Izza (2007)
Due to the globalization wave worldwide, many firms are competing for the international expansion. The firms change orientation from emphasis on creating a new product or service to marketing and this effort requires significant need of expatriation to realize the business goals globally. This study aims to identify the critical success factors (CSF) relating to expatriation by Malaysian Corporations operating internationally and identify a number of determinant factors that can be adopted by the Malaysian Corporations that operate internationally to enhance their viability in those countries. Besides, this study also aims to review the current issues related to expatriation; identify the factors that contribute to the success of expatriation by Malaysian Corporations and rank the factors contributing to the success or failure of expatriation by Malaysian Corporations. Self-administered questionnaire were developed to collect the primary data and were mailed to the Human Resource Managers of the companies extracted from the Federation of Malaysian Manufacturing (FMM) 2007 database